A deep learning and generative modeling pipeline for mining and engineering alkaline-stsable xylanases - Ruohan Zhang; Yiyang Zhang; Zhonghao Deng; Pengtao Wang; Lingxi Fan; Feng Guo; Huiying Luo; Yuan Wang; Tao Tu; Bin Yao; Jian Tian; Huoqing Huang; et al. (Bioresource Technology, 2026)

Host genotype-enriched rhizosphere microbes enhance pea (Pisum sativum L.) yield - Qinwen Yang; Qiong Liu; Ke Dong; Kaile Zhang; Chuanfa Wu; Ruohan Yin; Linying Xu; Zhijuan Feng; Tao Yang; Tida Ge (Plant and Soil, 2026)

A novel TpAQ-COF/ZnS/ZnIn2S4 ternary photocatalyst with double Z-scheme heterostructure for visible light photocatalytic degradation of 2,4-dichlorophenol - Ruohan Sun; Yuqing Xia; Tingting Ma; Hui Yu; Guixia Liu; Jinxian Wang; Wensheng Yu; Feng Sun; Xiangting Dong (Journal of Cleaner Production, 2026)

Generation of advanced glycation end products from glycated protein or fructose/glyoxal-protein adducts under in vitro simulated gastrointestinal digestion - Xiaojin Yuan; Shuqing Feng; Jianuo Li; Ruixin Guo; Chenxi Nie; Ruohan Zhai; Aobai Tu; Xinyu Cao; Min Zhang; Juxiu Li (Food Chemistry, 2025)

Inhibitory effects of potassium sorbate and ZnO nanoparticles on Escherichia coli and Staphylococcus aureus in milk-based beverage - Yuanyuan Zhang; Qianqian Yang; Feng Lu; Xiaoyang Wang; Ruohan Liang; Xiaodan Pu; Jianlei Chen; Dahai Zhang; Zhixiang Chen; Xuzhi Zhang (International Dairy Journal, 2024)

Selective activations and functional connectivities to the sight of faces, scenes, body parts and tools in visual and non-visual cortical regions leading to the human hippocampus - Edmund T. Rolls; Jianfeng Feng; Ruohan Zhang (Brain Structure and Function, 2024)
Connectivity maps are now available for the 360 cortical regions in the Human Connectome Project Multimodal Parcellation atlas. Here we add function to these maps by measuring selective fMRI activations and functional connectivity increases to stationary visual stimuli of faces, scenes, body parts and tools from 956 HCP participants. Faces activate regions in the ventrolateral visual cortical stream (FFC), in the superior temporal sulcus (STS) visual stream for face and head motion; and inferior parietal visual (PGi) and somatosensory (PF) regions. Scenes activate ventromedial visual stream VMV and PHA regions in the parahippocampal scene area; medial (7m) and lateral parietal (PGp) regions; and the reward-related medial orbitofrontal cortex. Body parts activate the inferior temporal cortex object regions (TE1p, TE2p); but also visual motion regions (MT, MST, FST); and the inferior parietal visual (PGi, PGs) and somatosensory (PF) regions; and the unpleasant-related lateral orbitofrontal cortex. Tools activate an intermediate ventral stream area (VMV3, VVC, PHA3); visual motion regions (FST); somatosensory (1, 2); and auditory (A4, A5) cortical regions. The findings add function to cortical connectivity maps; and show how stationary visual stimuli activate other cortical regions related to their associations, including visual motion, somatosensory, auditory, semantic, and orbitofrontal cortex value-related, regions.

Adsorption and photocatalytic degradation of quinolone antibiotics from wastewater using functionalized biochar - Ning Cheng; Bing Wang; Miao Chen; Qianwei Feng; Xueyang Zhang; Shengsen Wang; Ruohan Zhao; Tao Jiang (Environmental Pollution, 2023)

Different cortical connectivities in human females and males relate to differences in strength and body composition, reward and emotional systems, and memory - Ruohan Zhang; Edmund T. Rolls; Wei Cheng; Jianfeng Feng (Brain Structure and Function, 2023)
Sex differences in human brain structure and function are important, partly because they are likely to be relevant to the male–female differences in behavior and in mental health. To analyse sex differences in cortical function, functional connectivity was measured in 36,531 participants (53% female) in the UK Biobank (mean age 69) using the Human Connectome Project multimodal parcellation atlas with 360 well-specified cortical regions. Most of the functional connectivities were lower in females (Bonferroni corrected), with the mean Cohen’s d = − 0.18. Removing these as covariates reduced the difference of functional connectivities for females—males from d = − 0.18 to − 0.06. The lower functional connectivities in females were especially of somatosensory/premotor regions including the insula, opercular cortex, paracentral lobule and mid-cingulate cortex, and were correlated with lower maximum workload ( r = 0.17), and with higher whole body fat mass ( r = − 0.17). But some functional connectivities were higher in females, involving especially the ventromedial prefrontal cortex and posterior cingulate cortex, and these were correlated with higher liking for some rewards such as sweet foods, higher happiness/subjective well-being, and with better memory-related functions. The main findings were replicated in 1000 individuals (532 females, mean age 29) from the Human Connectome Project. This investigation shows the cortical systems with different functional connectivity between females and males, and also provides for the first time a foundation for understanding the implications for behavior of these differences between females and males.

Calcium alginate-nZVI-biochar for removal of Pb/Zn/Cd in water: Insights into governing mechanisms and performance - Ruohan Zhao; Bing Wang; Pan Wu; Qianwei Feng; Miao Chen; Xueyang Zhang; Shengsen Wang (Science of The Total Environment, 2023)

Recovery of nitrogen and phosphorus in wastewater by red mud-modified biochar and its potential application - Zhipeng Zhao; Bing Wang; Qianwei Feng; Miao Chen; Xueyang Zhang; Ruohan Zhao (Science of The Total Environment, 2023)

Alterations in functional network centrality in first-episode drug-naïve adolescent-onset schizophrenia - Ming Zhou; Lihua Zhuo; Ruofei Ji; Yingxue Gao; Hongchao Yao; Ruohan Feng; Lianqing Zhang; Guoping Huang; Xiaoqi Huang (Brain Imaging and Behavior, 2022)